Performance Management Dynamics of Short-Term Employees in A Non-Profit Educational Organization: A Study of Indonesia Teaches Movement - Dedi Kusuma Wijaya; Susan Murphy (ANIMA Indonesian Psychological Journal, 2017)
Departing from their roots in private-sector organizations, studies on performance management have extended to non-profit sector. However, most research comes from Western and/ or developed countries with more emphasis on permanent employees. This study outlined the performance management system in Indonesia Teaches Movement (ITM), a non-profit educational organization in Indonesia. It explored how performance management was implemented to “young teachers”, graduates from highly ranked universities who were recruited to work as teachers in remote and impoverished areas in Indonesia for one year. Data were collected through performance management-related archival data and semi-structured interviews with six “young teachers” and three ITM officers. Thematic analysis indicated that performance management cycle had been adopted by the organization despite a short tenure of the job. Results also revealed the roles of organizational vision and culture in harnessing performance and the strength of outcome mapping as strategic tools closely aligned with performance management. Ultimately, this study confirms that Performance Management is a dynamic and adaptive system that can be applied to non-profit organizations, particularly to non-permanent jobs with unconventional work arrangements.